2012
DOI: 10.1371/journal.pone.0048713
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Ablation of Foxm1 from Cardiomyocytes Causes Late Onset Cardiac Hypertrophy and Fibrosis without Exacerbating Pressure Overload-Induced Cardiac Remodeling

Abstract: Heart disease remains a leading cause of morbidity and mortality in the industrialized world. Hypertrophic cardiomyopathy is the most common genetic cardiovascular disorder and the most common cause of sudden cardiac death. Foxm1 transcription factor (also known as HFH-11B, Trident, Win or MPP2) plays an important role in the pathogenesis of various cancers and is a critical mediator of post-injury repair in multiple organs. Foxm1 has been previously shown to be essential for heart development and proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 42 publications
0
19
1
Order By: Relevance
“…This includes binding sites for transcription factors such as ATF2, FOXM1, STAT3, and MEF2A (Fig. 1B), which are reported to have roles in cardiac function either independently (16,17) or in cross-talk with the endothelin system (18,19). Also, within this cluster, the strongest signal was a 400-bp Chip-seq peak for the FOS/JUN (chr13:78503006-78503405; Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…This includes binding sites for transcription factors such as ATF2, FOXM1, STAT3, and MEF2A (Fig. 1B), which are reported to have roles in cardiac function either independently (16,17) or in cross-talk with the endothelin system (18,19). Also, within this cluster, the strongest signal was a 400-bp Chip-seq peak for the FOS/JUN (chr13:78503006-78503405; Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Although none of the SNPs were in the coding regions, many of these SNPs were overlying a cluster of transcription-factor binding sites identified in ENCODE ( Fig. 1 A and B), where the underlying transcription factors were reported to have roles in endothelin-mediated cardiac function (16,18,19). Promoter luciferase assay of the EDNRB gene indicated an 89-fold increased activity with an intact 1,258-bp promoter sequence and a further boost of 2.7-and 3.1-fold with overexpression of c-Jun or C/EBPb, respectively (21).…”
Section: Discussionmentioning
confidence: 99%
“…Its postnatal deletion from cardiomyocytes led to cardiac fibrosis (36), while on the other hand, its deletion from alveolar epithelial cells protected against radiationinduced pulmonary fibrosis and epithelial-mesenchymal transition (EMT) (37). Recent studies using lineage tracing to explore the origins of myofibroblasts -the ultimate effectors of tissue fibrosis -in models of lung fibrosis have concluded that an in vivo role for EMT is either absent or minimal (38)(39)(40) and instead emphasize the importance of resident lung fibroblasts as their major source (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Expression of an activated Kras G12D in respiratory epithelial cells impaired branching lung morphogenesis, increased MAPK activity and induced expression of Sprouty-2, a Ras/ERK antagonist (Shaw et al, 2007). Foxm1 transcription factor is a key downstream target of the Kras/ERK signaling pathway and an important regulator of cellular proliferation during embryonic development, organ injury and carcinogenesis (Bolte et al, 2011(Bolte et al, , 2012Balli et al, 2012;Sengupta et al, 2013;Cheng et al, 2014;Xia et al, 2015). Kras downstream kinases, including ERK, Cdk1, and Cdk2, directly phosphorylate Foxm1 and induce its transcriptional activity (Major et al, 2004;Ma et al, 2005).…”
Section: Introductionmentioning
confidence: 99%